Tropical Dissidence: The Creation of the School of Architecture of the University of Costa Rica at the Department of Development and Tropical Studies. Issue 2 (4th May 2017) - Solano-Meza, Natalia
Abstract: In 1971, the School of Architecture of the University of Costa Rica ARQUIS opened with an experimental programme that claimed that "the better the education, the more unpredictable the results." The programme had been partially devised at the Department of Tropical Studies of the Architectural Association by three Costa Rican architects: Felo García, Jorge Bertheau and Edgar Brenes who attended the Department's Teaching Methods course in 1970. Upon their return to Costa Rica, the team confronted the University's authorities, the expectations of professional organisations such as the Costa Rican Architects Association and the critiques of their peers in implementing the School's programme. This paper explores the process that led to the opening of the School of Architecture, the role of the Department of Tropical Studies in its creation, its defiant propositions and the ways it challenged the expectations of the Costa Rican academy during its opening years. It explores the concept of "tropical dissidence": the rejection of inherited European methods – both in teaching and design – and their substitution with context-observation-based exercises, in the tradition of the Department of Tropical Studies. The School's efforts were aimed at obtaining local architectural solutions in Costa Rica and increasing the participation of architects in national matters. This paper proposes that the School challenged traditional education to achieve operational freedom and primal autonomy.